The Pattern of Local Cassava-Based Processed Food Choice in Lampung Province - Sayekti, Wuryaningsih Dwi; Lestari, Dyah Aring Hepiana; Ismono, Raden Hanung (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractLocal food is a potential commodity in food consumption diversification. Tapioca vermicelli and “siger” rice are two local foods developed in Lampung Province. However, these products have not brought any contribution to the community's food consumption pattern. The objective of this study is to analyze the choice pattern and any factors relating to the choice of tapioca vermicelli and “siger” rice. This research used a quantitative research approach with a survey method. It was conducted in Metro City and Pringsewu Regency with a sample of 110 households. The analysis of Chi-Square descriptive statistics and correlation was used to analyze the data. The results of the research found that tapioca vermicelli is quite popular (widely chosen) by the families living around the agroindustrial area of Metro City. However, “siger” rice is not widely used by people in this location. Tapioca vermicelli is consumed more often with meatballs in a medium frequency and total consumption of 45.33 grams/ household/day. “Siger” rice is consumed as a variation with rare consumption, and its average consumption amount is 9.34 grams/household/day. Any variables related to vermicelli tapioca choice are knowledge level on food diversification, education level, age, household income and knowledge level on nutrition. Whereas, any factors related to “siger” rice choice are product identification, knowledge of food diversification and accessibility. Keywords: food choice patterns, local food, “siger” rice, tapioca vermicelli